Voices from the Warsaw Ghetto : writing our history - Roskies, David G., 1948-; Kassow, Samuel D. (New Haven [Connecticut] : Yale University Press, 2019)
"The powerful writings and art of Jews living in the Warsaw Ghetto. Hidden in metal containers and buried underground during World War II, these works from the Warsaw Ghetto record the Holocaust from the perspective of its first interpreters, the victims themselves. Gathered clandestinely by an underground ghetto collective called Oyneg Shabes, the collection of reportage, diaries, prose, artwork, poems, jokes, and sermons captures the heroism, tragedy, humor, and social dynamics of the ghetto. Miraculously surviving the devastation of war, this extraordinary archive encompasses a vast range of voices--young and old, men and women, the pious and the secular, optimists and pessimists--and chronicles different perspectives on the topics of the day while also preserving rapidly endangered cultural traditions. Described by David G. Roskies as "a civilization responding to its own destruction," these texts tell the story of the Warsaw Ghetto in real time, against time, and for all time." --
Oyneg Shabes / Emanuel Ringelblum -- Telephone / Władysław Szlengel -- I speak to your openly, child / Josef Kirman -- Ghetto folklore / Shimon Huberband -- House no. 21 / Peretz Opoczynski -- Chronicle of a single day / Leyb Goldin -- From Scroll of agony / Chaim A. Kaplan -- Charcoal and watercolor sketches (1939-42) / Gela Seksztajn -- The little smuggler / Henryka Łazowert -- Hershek / Stepania Gradzińska -- Song of hunger and songs of the cold / Yitzhak Katzenelson -- From Holy fire / Rabbi Kalonymus Shapira -- From the Notebooks and diary of the great deportation / Abraham Lewin -- Last testament / Israel Lichtenstein -- What can I possibly say and ask for at this moment? / Gela Seksztajn -- 4580 / Yehoshue Perle -- Things and counterattack / Władysław Szlengle -- The ghetto in flames / "Maor" -- Yizkor, 1943 / Rachel Auerbach
"A companion volume to the Posen Library of Jewish Culture and Civilization."
Includes bibliographical references (pages 245-247)
Description based on online resource; title from digital title page (OverDrive ebook, viewed on August 28, 2023).
JSTOR
Keywords: Oyneg Shabes (Group); Oyneg Shabes (Group); Jews -- Persecutions -- Poland -- Warsaw -- History -- Sources; Holocaust, Jewish (1939-1945) -- Poland -- Warsaw -- Sources; Holocaust, Jewish (1939-1945) -- Poland -- Warsaw -- Personal narratives; Getto warszawskie (Warsaw, Poland); Jews -- Poland -- Warsaw -- Biography; World War, 1939-1945 -- Jews -- Poland -- Warsaw -- Sources; World War, 1939-1945 -- Personal narratives, Jewish; Warsaw (Poland) -- History -- 20th century -- Sources; Juifs -- Persécutions -- Pologne -- Varsovie -- Histoire -- Sources; Holocauste, 1939-1945 -- Pologne -- Varsovie -- Sources; Holocauste, 1939-1945 -- Pologne -- Varsovie -- Récits personnels; Juifs -- Pologne -- Varsovie -- Biographies; Guerre mondiale, 1939-1945 -- Juifs -- Pologne -- Varsovie -- Sources; Guerre mondiale, 1939-1945 -- Récits personnels juifs; Varsovie (Pologne) -- Histoire -- 20e siècle -- Sources; HISTORY -- Europe -- Western; HISTORY -- Holocaust; Jews; Jews -- Persecutions; Poland -- Warsaw; Poland -- Warsaw -- Getto warszawskie; 1900-1999; Electronic books; Personal Narrative; Biography; Biographies; History; Personal narratives; Personal narratives -- Jewish; Sources; Personal narratives; Biographies; Récits personnels; Biographies